The Strategy of the Madrasah Head in Improving the Religious Culture of Students at M. A Manbaul Ulum Mojopuro Gede Gresik Jawa Timur - Zaini, Mohammad (International Journal of Educational Research & Social Sciences, 2023)
Realizing an educational institution development strategy, it must have a management strategy that is able to nourish the institution and lead to significant progress that is able to develop a religious culture. This type of research is qualitative research, based on the discussion including descriptive research using a multi-case study design. Data collection techniques using observation, interviews, and documentation. Data analysis was carried out starting from data reduction, data presentation, and drawing conclusions. The research results arePrincipal Planningin the Development of Religious Culture at MA Manbaul Ulum Mojopuro Gede Gresik, East Java, there is already a good program planning, namely: a) Daily Activities, namely Tadarus of the Qur'an in the morning, Memorizing prayers and dhikr, Dhuha Prayers and Dhuhur Prayers in congregation. b) Weekly activities namely Reading Asmaul Husna, Friday charity and c) incidental or temporal activities.ImplementationThe Principal in the Development of Religious Culture at MA Manbaul Ulum Mojopuro Gede Gresik, East Java by implementing several activities, namely: Daily religious activities, weekly religious activities, incidental religious activities.Principal Evaluationin the Development of Religious Culture at MA Manbaul Ulum Mojopuro Gede Gresik, East Java, can be seen from: a) Students fill out the attendance list, b) Monitoring from the madrasa, the head of the madrasa always provides guidance to all madrasa residents. c) Giving sanctions by the head of the madrasa is very good to do, so that the programs in the school principal of the madrasa not only support it, but also contribute to its implementation to the fullest.